OFFICE BASE MANAGEMENT OF NON-PROLAPSED INTERNAL HEMORRHOIDS: SINGLE VERSUS DOUBLE BAND LIGATION - Tahir Iqbal Mirza (Army Medical College Rawalpindi, 2019)
Objective: To compare single versus double band ligation in the office based management of non-prolapsed internal hemorrhoids.